Iodine-Mediated Neutral and Selective N-Boc Deprotection. (27th June 2013) - Pavan Kumar, G.; Rambabu, D.; Basaveswara Rao, M. V.; Pal, Manojit
Abstract : A simple, efficient, and alternative method has been developed for the N -Boc deprotection of structurally diverse protected amines. Selective removal of N -Boc groups was achieved with excellent yields under a solvent-free condition or in a solvent using iodine as a catalyst. The methodology involving the first use of iodine for N -Boc deprotection of protected amines represents an effective and useful alternative to the previously reported methods.